Change in Alcohol Consumption and Binge Drinking in University Students During the Early COVID-19 Pandemic - Zysset, Annina; Volken, Thomas; Amendola, Simone; von Wyl, Agnes; Dratva, Julia (Frontiers in Public Health, 2022)
Objectives Young adults have been overly affected by the containment measures against COVID-19 and, consequently, worsening in mental health and change in health behavior have been reported. Because the life phase of emerging adulthood is crucial for developing health behaviors, this study aims to examine increase in alcohol consumption, single and multiple binge drinking, and associated factors in students during lockdown and post-lockdown periods. Methods A prospective open cohort study design with nine survey time points between April 2020 and June 2021 was conducted. The present study uses pooled data from the first survey T0 (3 April to 14 April) and follow-ups at T1 (30 April to 11 May 2020) and T2 (28 May to 8 June 2020). Students from all faculties of the Zurich University of Applied Sciences (ZHAW) (N = 12'431) were invited. Of the 1,300 students who participated at baseline and in at least one follow-up, 1,278 (98.3%) completed the questionnaires, final net sample size was 947. Generalized Estimating Equations (GEE) models were used to investigate the factors associated with increases in alcohol consumption based on number of occasions/last 30 days; drinks/week, and binge drinking at T0, and respective changes at T1 and T2 (increases, decreases, no change). Results Overall, 20% of Swiss university students reported an increased alcohol consumption and 26% engaged in binge drinking. Number of drinks at baseline was associated with a higher probability of increased alcohol consumption, as well as engaging in single and multiple binge drinking events. Higher anxiety scores were associated with a higher probability to increase the alcohol consumption and engaging at least once in binge drinking. Additional factors associated with any binge drinking were male gender, younger age and not living with parents. Higher perceived social support was only associated with engaging in heavy binge drinking. Conclusions A substantial number of students developed a more risky health behavior regarding alcohol consumption. It is important to identify at risk students and design target prevention including factors such as age, gender and social norms. Further, health behavior and determinants of health behaviors of students should be carefully monitored during the further course of the pandemic.